POTENSI DAN PEMANFAATAN BAHAN AKTIF ALGA COKELAT SARGASSUM SP - Chalvyn S. Pakidi; Hidayat Suryanto Suwoyo (Universitas Muhammadiyah Makassar, 2017)
In Indonesia there are many types of seaweed that have economic value is high enough one of them Sargassum sp containing alginate material and iodine that are used in the food industry, pharmaceuticals, cosmetics and textiles. It also Sargassum sp. steroid containing active compounds, alkaloids, phenols, and triterpenoids acts as an antibacterial, antiviral, and antifungal. This study aims to assess the potential and utilization of active compound contained in brown algae Sargassum sp and its application in the field of fisheries. The study results were Obtained that the species Sargassum sp. known in Indonesia there are about 15 species. Sargassum sp. can be used as anti-cholesterol, biofuels, biofertilizer, antibacterial, antitumor, anticancer, antifouling, antivirus and cosmetic creams. Extract Sargassum sp. Also has potential as an antioxidant and as a raw material for making surfactant. Sargassum extract applications in the field of fisheries could be used to inhibit the growth of bacteria Vibrio sp the which is a cause of disease firefly glow of the most dangerous for black tiger shrimp